International student experience in Indonesia and public diplomacy consequences: Governance of Darmasiswa program - Aldila Maharani Sutjipto; Janette Maria Pinariya; Fiona Suwana (Institute of Advanced Engineering and Science, 2023)
This study discussed Darmasiswa program as Indonesia’s public diplomacy effort in the educational fields conducted by the Republic Indonesia Ministry of Education, Culture, Research, and Technology (Kemendikbud RI). Despite its vast opportunities, Indonesia still has difficulties attracting international students compared to various neighboring countries. By analyzing the seven pillars of public diplomacy, supported by international communication and industry 4.0 concept, this study showed that Kemendikbud has considered the seven pillars in public diplomacy in conducting public diplomacy efforts. It is found that Darmasiswa is a state-directed effort designed to enhance favorable international relations through the student movement’s positive experience. The strategy is formed by uses various types of communication channels that support each other’s. The message is also processed by involving policy and rationality by prioritizing consistent, truthful, and credible as part of the main elements. Besides, they form strategies by maximizing cooperation with various parties. In Kemendikbud, the program undertakes audience research and actors from 1st and 2nd track diplomacy as part of its tactics. The program also found that public diplomacy in Darmasiswa program has acknowledged changes in the 4.0 era through new media usage. However, there are still many challenges encountered in the performance of the seven pillars.